Design of sodium lanthanide fluoride nanocrystals for NIR imaging and targeted therapy. (January 2023) - Min, Yu; Ding, Xin; Yu, Bing; Shen, Youqing; Cong, Hailin
Abstract: Since the 18th century, rare-earth ions have been widely used as active dopants in inorganic lattices due to their unique optical properties. Rare-earth doping can control the crystal phase, morphology and size of nanomaterials, resulting in adjustable optical response of doped nanomaterials. The substrate of nanostructures can greatly affect the physical and chemical behavior of rare-earth ions. Therefore, it is also important to find suitable host materials. Among various new host materials, sodium lanthanide fluoride (NaLnF4 ) nanoparticles are known for their photoluminescence properties and stability. This paper emphasizes the latest progress of NaLnF4 and its derivatives nanoparticles and their related applications in various biological fields. This review covers the key criteria of NaLnF4 and its derivatives, including basic electronic structure, lattice environment, doping strategy, surface functionalization and basic design principles for biological applications. At the same time, this paper also discusses the obstacles encountered in the development process and the research directions and challenges of future new applications. Highlights: NaLnF4 and its derivatives in application of bioimaging, biosensing and multifunctional nanoplatform. NaLnF4 and its derivatives can obtain adjustable emission range and fluorescence intensity . NaLnF4 and its derivatives have been developed into a non-invasive diagnostic platform.